GOVERNMENT PARTNERSHIP SOCIAL ENTREPRENEURS IN POVERTY ALLEVIATION - Umi Hani (JEES: Journal of Economic Empowerment Strategy, 2019)
The ASEAN Economic Community (AEC) has an influence on the Indonesian state, one of which is its influence in the economic field. With the AEC providing opportunities for people to be more creative and innovate such as by carrying out social entrepreneurship activities, which social entrepreneurship is a good opportunity for the community to face the AEC 2015. Social entrepreneurship is considered as a solution in an effort to accelerate the reduction in unemployment and poverty. This is none other than because social entrepreneurship offers advantages over just creating jobs. One of the goals of social entrepreneurship is to overcome the problem of poverty. The problem of poverty is a condition where a person is unable to fulfill his basic needs such as food, clothing, shelter, education, and proper health. The purpose of this study is to find out whether social entrepreneurship can help the government in poverty alleviation. This study uses a qualitative approach , a qualitative approach is a way of researching to reveal problems by describing and explaining phenomena in the present that occur in accordance with the facts in the field, so as to produce data that is poured into a scientific paper.The results of the study explained that in the face of the ASEAN economic community (AEC), the government must prepare everything. This was done so that the people of Indonesia were not surprised and could follow the flow of the AEC. In dealing with MEA, the government can hold social workers (social work) as socioworkpreneur in carrying out social entrepreneurial practices one focus is on community empowerment, not only the problem of opening employment but rather towards growing self-reliance of the community members means growing mentality and attitude as entrepreneurship itself